Bráðar kransæðaþræðingar á Íslandi : árangur á fyrsta ári sólarhringsgæsluvaktar - Berglind Gerda Libungan; Kristján Eyjólfsson; Guðmundur Þorgeirsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2008)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open INTRODUCTION: Acute coronary angiography with primary percutaneous coronary intervention (PCI), if executed with sufficient expertise and without undue delay, is the best therapy for patients with ST-elevation myocardial infarction (STEMI). At Landspitali-University Hospital 24 hour on-call service has been provided since December the 1st 2003. This hospital is the single center for all coronary catherizations in Iceland. This report is a review of this service during the first year. PATIENTS AND METHODS: Retrospective review was carried out of all hospital records and PCI worksheets of those who had an acute coronary angiography from December 1st 2003 until November 30th 2004. RESULTS: A total of 124 patients were investigated with acute coronary angiography, 94 men (76%) and 30 women (24%). The average age of men was 61 years (range 19 to 85 years) and women 67 years (range 38 to 84 years). The primary indication for acute coronary angiograpy was STEMI (83%), 8% non ST-elevation myocardial infarction (NSTEMI) and for the remaining 9% the procedure was performed for other reasons. Eleven patients (9%) suffered cardiac arrest prior to angiography and ten (8%) were in cardiogenic shock upon arrival to the hospital. The mean door-to-needle time was 47 minutes for all STEMI patients. In 76% of the cases the procedure started within 60 minutes and in 91% within the recommended 90 minutes. Mean hospital stay was 5 (1/2) days. Total mortality was 7% (9 patients). Of those 9 patients 5 were in cardiogenic shock at the arrival to the hospital and 4 had suffered cardiac arrest. The mortality rate among those who were neither in cardiogenic shock upon admission nor having suffered cardiac arrest was 1,7% (2 patients). During follow up for 15-27 months nine of the patients needed CABG and nine needed a repeat PCI. CONCLUSION: The experience of a 24 hour on-call service at Landspitali-University Hospital to carry out primary ...